Rola przedstawień drzewa genealogicznego zakonu w środowisku premonstratensów - Kwiatkowska-Frejlich, Lidia (Archiwa, Biblioteki I Muzea Kościelne, 2013)
The commonly known representation of Tree of Jesse, as inspired by the words „And the wand will come out of the root of Jesse and a flower will grow out of from its root” (Isaiah 11:1), proves the interpersonal relationships with Jesus and His messianic prophecy - by indicating on David. But since the earliest times this theme has been explored in the secular art because branching limbs with characters of descendants, growing from the parents’ chest, clearly illustrate the relations resulting from successions of generations within the family framework. This kind of representations was also popular in orders. At that time they not only provided the information on the background of spiritual path but also the assurance of its effectiveness on the way to reach Heaven. The images of the Order of Canons Regular of Prémontré, also known as the Premonstratensians, elaborated upon in this paper, was to make canons regular believe that abiding by the rules and laws made by the Order and praising the Eucharist, canons regular may master themselves to perfection and the saints of the order, who had already successfully fulfilled this recommendation, were the best teachers on the path of spiritual progress.
Keywords: 📚 premonstratensian (general)

O dawnych zwyczajach prawnych w swietle materialów procesovvych klasztoru sw. Wincentego na Oibinic we Wroclawiu z XIV wieku - Mlynarska-Kaletynowa, Marta (Z badan nad kultura spoleczenstw pradziejowych i wczesnosredniowiecznych: ksiega jubileuszowa dedykowana profesorowi Boguslawowi Gedidze, w osiemdziesiata rocznice urodzin przez przyjaciól, kolegów i uczniów, 2013)
Keywords: wrocław

Fundacja Opactwa Premonstratensów w Brzesku-Hebdowie - Podgórska, Arkadia (Meandry Historii: Starożytność – średniowiecze – nowożytność. Referaty wygłoSzone na XX ogólnopolskim zjeździe Historyków Studentów w Katowicach, 2013)
Keywords: brzesko